2012
DOI: 10.1002/ps.3383
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide susceptibility status in three medically important species of mosquitoes, Anopheles stephensi, Aedes aegypti and Culex quinquefasciatus, from Bruhat Bengaluru Mahanagara Palike, Karnataka, India

Abstract: The genome information is offering opportunities to manipulate genes, polygenic characters and multiple traits in plants. Although a number of approaches have been developed to manipulate traits in plants, technical hurdles make the process difficult. Gene cloning vectors that facilitate the fusion, overexpression or down regulation of genes in plant cells are being used with various degree of success. In this study, we modified gateway MultiSite cloning vectors and developed a hybrid cloning strategy which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 55 publications
(65 reference statements)
0
20
0
Order By: Relevance
“…aegypti in Delhi. Insecticide susceptibility tests carried out in India by several authors prior to the year 2014 did not reveal pyrethroid resistance, though they were found to be resistant to DDT [30] – [33] . Only in one case, 2% survival was recorded in Aedes aegypti on exposure to diagnostic concentration of deltamethrin in a strain from Jharkhand, India [30] .…”
Section: Discussionmentioning
confidence: 99%
“…aegypti in Delhi. Insecticide susceptibility tests carried out in India by several authors prior to the year 2014 did not reveal pyrethroid resistance, though they were found to be resistant to DDT [30] – [33] . Only in one case, 2% survival was recorded in Aedes aegypti on exposure to diagnostic concentration of deltamethrin in a strain from Jharkhand, India [30] .…”
Section: Discussionmentioning
confidence: 99%
“…They are the most geographically widespread and medically important vectors of human disease (Hickner et al ., ). Mosquito‐borne tropical diseases, such as malaria, dengue and filariasis, continue to be significant causes of morbidity and mortality in several countries (Shetty et al ., ). Chemical control is the main method to control mosquitoes, and previous resistance investigations showed that mosquitoes in China had become resistant to organophosphates (OP), organochlorines and pyrethroids (Cui et al ., ; Liu et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Susceptibility studies for various classes of insecticides, including organochlorines, organophosphates, carbamates, synthetic pyrethroids and botanicals, have been carried out on three major mosquito vector species (Ghosh et al, 2002;Kashyap and Shetty, 2011;Shetty et al, 2006Shetty et al, , 2007Shetty et al, , 2010Shetty et al, , 2012. The genetic basis of chlorpyrifos (Chandrakala and Shetty, 2006) and propoxur (Sanil and Shetty, 2010) resistance and their cytological basis (Shetty et al, 2013) have been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Application of inappropriate insecticides without an understanding of the prevailing resistance mechanisms may lead to control failure. Hence, periodic monitoring of insecticide resistance status is an important criterion in vector control programmes (Shetty et al, 2012). The rate at which an insecticide becomes ineffective depends on the selection pressure for resistance, which is determined by monitoring, and how often and for how long the insecticide is being used (Hudson, 1983).…”
Section: Discussionmentioning
confidence: 99%